The house that Jack built - Trier, Lars von, 1956-; Ganz, Bruno; Dillon, Matt; Keough, Riley, 1989-; Thurman, Uma; Scream Factory (Firm); IFC Films (IFC Films, Scream Factory, 2020)
The story follows Jack, a highly intelligent serial killer throughout twelve years and depicts the murders that truly develop Jack as a serial killer.
Disc 1: theatrical cut, trailer -- Disc 2: director's cut, interview with director.
Originally released as a motion picture in 2018.
Special features: theatrical trailer ; interview with director.
Bruno Ganz, Matt Dillon, Riley Keough, Uma Thurman, Jeremy Davies, Siobhan Fallon.
Rating: R; for strong disturbing violence/sadistic behavior, grisly images, language, and nudity. The unrated director's cut contains material different from the original R-rated version.
DVD, wide screen 2.40:1, Dolby 5.1 and stereo, region 1.
English dialogue; English or Spanish subtitles.
Keywords: Video recordings for the hearing impaired; Serial murderers -- Drama; Genius -- Drama; Feature films; Crime films; Horror films; Fiction films